Deceptive Practices Used in Contemporary Marketing Communication and their Evaluation from Customer Perspective in Slovak Republic - Gubiniova, Katarina; Bartakova, Gabriela Pajtinkova (International Review of Management and Marketing, 2017)
Satisfying customer needs in order for an organisation to achieve a defined profitability on the one hand and to have satisfied customers on the other has been characteristic of traditional customer-oriented approaches to marketing management. Hypercompetitive market, which is currently functioning at the level of both national and multinational economies, is characterised by the fact that in an effort of marketing managers to operate in markets, more and more deceptive, unethical and misleading practices are appearing. Misleading, deceptive and unethical approaches of marketing management have become a subject of social criticism, while this issue is gradually becoming more and more notable also in academic sphere. Therefore, perception and evaluation of the marketing activities in marketing communication by ultimate customers under the conditions of the Slovak Republic (on the grounds of a research with the participation of a representative sample size of 1,820 respondents) are dealt with in this paper. Keywords: Marketing communication, Deceptive practices, Perception of deceptive practices by ultimate customers. JEL Classifications: M31, M37